The Effect of Human Resource Information System (HRIS) Integration, Conflict Management, and Work Flexibility on Work-Life Balance in Banten Manufacturing Industry - Palupiningtyas, Dyah; Nurisman, Husain; Syafri, Muhammad; Vandika, Arnes Yuli; Amalia, Mei Rani (Westscience Press, 2024)
Within the context of the manufacturing sector in Banten, this research explores the impact that the integration of Human Resource Information Systems (HRIS), conflict management, and work flexibility have on the work-life balance of employees operating in that sector. Through the use of a quantitative research methodology, data were gathered from a total of 160 samples by means of a structured questionnaire that utilized a Likert scale that ranged from 1 to 5. Through the utilization of Structural Equation Modeling-Partial Least Squares (SEM-PLS 3), the data were examined in order to determine the links that exist between the variables. According to the findings, high-resolution information system (HRIS) integration considerably improves work-life balance by optimizing human resource operations and increasing employee access to information. Effective conflict management practices are shown to mitigate workplace tensions, further contributing to a better work-life balance. Additionally, work flexibility is found to be a crucial factor in allowing employees to manage their professional and personal responsibilities more effectively. The study underscores the importance of integrating advanced HR systems, adopting robust conflict management strategies, and promoting flexible work arrangements to enhance the work-life balance of employees in the manufacturing sector.